ONRECHTMATIG OVERHEIDSDAAD BY THE GOVERNMENT ON THE LIABILITY OF THE GOVERNMENT REGULATION (CASE STUDY ON LAW NUMBER 18 OF 2017) - Khafifah, Nur Rizqi; Minan, Ahsanul; Rusydi, Muhammad (Jurnal Poros Hukum Padjadjaran, 2023)
This paper discusses about "Government Actions Against the Obligation to Prepare Government Regulations from Law No.18 of 2017" in the form of a Legal Memorandum. Where the Government in making and issuing Government Regulations from Law No. 18 of 2017 has exceeded the time limit that has been regulated in in law. The legal questions that arise are (1) is the government's attitude that exceeds the time in issuing the Government Regulations an act of the government in carrying out government administration functions? (2) Is the government's attitude exceeding the time in issuing the Government Regulations a violation of State Administration law? This study uses normative legal analysis. The purpose of this writing is the invention of recommendation given by the author for consideration to readers and the people of Indonesia, especially is those who feel be anggrieved by the government’s actions in the state arrangement. The results of the analysis of this Legal Memorandum conclude that the government's action is an administrative function of the government and is an unlawful act. As for the recommended recommendations, citizens who feel aggrieved by the government's actions can take repressive actions against government actions from Law No.18 of 2017, these citizens can sue the President to the State Administrative Court as an authorized court according to law after committing administrative effort.